The Influence Of Using The Quizizz Application On Student Engagement In Fiqh Subjects At SMA Muhammadiyah 3 Surakarta - Hasanah, Fadhilah; Subando, Joko (Yayasan Rahmat Islamiyah, 2025)
This study aims to examine the influence of using the Quizizz application on student engagement in Fiqh learning at SMA Muhammadiyah 3 Surakarta. This research employs a quantitative approach with a quasi-experimental design, involving two groups: the experimental group (using Quizizz) and the control group (using conventional methods). Data were collected through observation and questionnaires, and analyzed using a t-test. The results showed that students in the experimental group were significantly more active than those in the control group. Visual, listening, motor, and verbal participation aspects were more dominant in the experimental group. The use of Quizizz not only increased student motivation and engagement but also made it easier for teachers to conduct real-time assessments. Therefore, Quizizz can serve as an effective technology-based learning strategy to enhance student participation, particularly in subjects that are typically perceived as monotonous.